Arbuscular mycorrhizal fungi enhance photosynthesis, water use efficiency, and growth of frankincense seedlings under pulsed water availability conditions - Birhane, Emiru; Sterck, Frank J.; Fetene, Masresha; Bongers, Frans; Kuyper, Thomas W. (Oecologia, 2012)
Under drought conditions, arbuscular mycorrhizal (AM) fungi alter water relationships of plants and improve their resistance to drought. In a factorial greenhouse experiment, we tested the effects of the AM symbiosis and precipitation regime on the performance (growth, gas exchange, nutrient status and mycorrhizal responsiveness) of Boswellia papyrifera seedlings. A continuous precipitation regime was imitated by continuous watering of plants to field capacity every other day during 4 months, and irregular precipitation by pulsed watering of plants where watering was switched every 15 days during these 4 months, with 15 days of watering followed by 15 days without watering. There were significantly higher levels of AM colonization under irregular precipitation regime than under continuous precipitation. Mycorrhizal seedlings had higher biomass than control seedlings. Stomatal conductance and phosphorus mass fraction in shoot and root were also significantly higher for mycorrhizal seedlings. Mycorrhizal seedlings under irregular watering had the highest biomass. Both a larger leaf area and higher assimilation rates contributed to higher biomass. Under irregular watering, the water use efficiency increased in non-mycorrhizal seedlings through a reduction in transpiration, while in mycorrhizal seedlings irregular watering increased transpiration. Because assimilation rates increased even more, mycorrhizal seedlings achieved an even higher water use efficiency. Boswellia seedlings allocated almost all carbon to the storage root. Boswellia seedlings had higher mass fractions of N, P, and K in roots than in shoots. Irregular precipitation conditions apparently benefit Boswellia seedlings when they are mycorrhizal.